Tumor-induced Osteomalacia in a Boy with Maxillary Ossifying Fibroma - Ha Nguyen Thi; Cuong Pham Manh; Linh To Tuan; Lan Anh Le Thi; Nam Nguyen Thanh; Soamarat Vilaiyuk (Galenos Yayincilik, 2023)
Tumor-induced osteomalacia (TIO) is a rare, paraneoplastic disorder of hypophosphatemia associated with elevated tumor-produced fibroblast growth factor 23 (FGF23). Maxillofacial tumors are rarely involved in TIO, especially maxillary TIO in children. We present a 14-year-old boy with osteomalacia and high serum levels of FGF23, a hormone associated with decreased phosphate resorption, due to a maxillary tumor. The patient was treated with oral phosphorus and calcitriol, and surgical removal of the tumor was performed. After 21 months follow-up, he was pain free and had returned to full activity. We review the reported pediatric cases of TIO in the maxillofacial and oral region and discuss the management of these patients considering the published evidence.